(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Appropriate nutrient management could increase crop productivity in saline areas by reducing the harmful effects of soil salinity. A field experiment was carried out at farmer’s field of Botiaghata, Khulna to investigate the mitigation of soil salinity by efficient management of potassium and zinc fertilizers in rice. BRRI dhan53, a salt-tolerant rice cultivar during aman season, was used as a test crop. The experiment was laid out in a randomized complete block design with three replications where sixteen treatment combinations were used in a factorial arrangement. Potassium and zinc nutrients were supplied from potassium sulphate and zinc sulphate, respectively and they were applied in two splits, first split during final land preparation and second split at maximum tillering stage. Recommended doses of N, P and S fertilizers were applied to all the experimental plots. Results revealed that plant height, panicle length, number of effective tillers and grains per panicle increased significantly due to application of K and Zn fertilizers. All the yield contributing parameters showed higher values in T15 (K200Zn200) treatment compared to other treatments. Grain and straw yields of BRRI dhan53 responded significantly to the different treatment combinations. The highest grain yield (4.46 t/ha) was obtained in T15 (K200Zn200) treatment and the highest straw yield (6.27 t/ha) was also obtained in the same treatment. Higher doses of potassium and zinc also increased nutrient uptake (N, P, S and Zn) by BRRI dhan53. The K+/Na+ ratio was also found higher in grain (0.319) and straw (0.301) in T15 treatment. Therefore, result of the experiment indicated that application of higher doses of K and Zn fertilizers could alleviate the adverse effects of salinity in rice production by increasing nutrient uptake and maintaining higher K+/Na+ ratio. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (3), 154-161